Interactive education in public administration (1): The role of teaching 'objects'. (September 2014) - Alford, John; Brock, Jonathan
Schools of public policy and administration are increasingly adopting interactive case teaching (long used in business schools) as one of their primary pedagogical methods – not least because of its usefulness in both stimulating engagement by students and helping them turn that engagement into learning. This article and its companion piece (Interactive education in public administration (2): Strategies for teachers) acknowledge and explain this usefulness, but go beyond cases to also include other forms of what we call teaching 'objects'. Starting with an outline of the educational rationale of interactive teaching, this article explains the nature of 'objects', how they enhance learning, their relevance specifically to public policy and administration, and what distinguishes good from poor objects. It focuses primarily on why teaching objects are used. The companion article sets out how to use them, laying out strategies for instructors.